2021
DOI: 10.1038/s41401-020-00601-4
|View full text |Cite
|
Sign up to set email alerts
|

Berberine alleviates visceral hypersensitivity in rats by altering gut microbiome and suppressing spinal microglial activation

Abstract: Accumulating evidence shows that agents targeting gut dysbiosis are effective for improving symptoms of irritable bowel syndrome (IBS). However, the potential mechanisms remain unclear. In this study we investigated the effects of berberine on the microbiota-gut-brain axis in two rat models of visceral hypersensitivity, i.e., specific pathogen-free SD rats subjected to chronic water avoidance stress (WAS) and treated with berberine (200 mg· kg−1 ·d−1, ig, for 10 days) as well as germ-free (GF) rats subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 68 publications
1
32
0
Order By: Relevance
“…These changes appear to be due to the action of the potential prebiotic berberine. It has been reported that berberine can alter the structure of the intestinal microbiota and reduce the a diversity (40), which is consistent with the results of the present study. In the combined Chinese and Western drugs group, FT3 and FT4 were negatively correlated with Faecalibacterium prausnitzii, TSH was positively correlated with Faecalibacterium prausnitzii, and Lactococcus lactis showed a strong negative correlation with FT4, indicating a close relationship between thyroid indicators and the microbiota.…”
Section: Discussionsupporting
confidence: 94%
“…These changes appear to be due to the action of the potential prebiotic berberine. It has been reported that berberine can alter the structure of the intestinal microbiota and reduce the a diversity (40), which is consistent with the results of the present study. In the combined Chinese and Western drugs group, FT3 and FT4 were negatively correlated with Faecalibacterium prausnitzii, TSH was positively correlated with Faecalibacterium prausnitzii, and Lactococcus lactis showed a strong negative correlation with FT4, indicating a close relationship between thyroid indicators and the microbiota.…”
Section: Discussionsupporting
confidence: 94%
“…Second, gut microbiome is an important target of BBR. Recently, we have demonstrated that BBR ameliorates ovariectomy-induced anxiety-like behaviors and visceral hypersensitivity by regulating the gut microbiome ( Fang et al, 2021 ; Zhang et al, 2021 ). In the current study, we cannot fully exclude the possibility that the gut microbiome might be involved in BBR preventing PC lung metastasis However, we propose that the direct modulation of BBR on TC-EC interaction might play a major role in the anti-metastatic effect of BBR.…”
Section: Discussionmentioning
confidence: 99%
“…The use of berberine in diabetic rats resulted in an increase in the number of Bacteroidetes and Lactobacillaceae, and a decrease in the number of Proteobacteria and Verrucomicrobia [134]. In contrast, in rats subjected to chronic stress, berberine increased the abundance of Verrucomicrobia, Bacteroides, Lachnoclostridium, Akkermansia, and Anaerostipes, and decreased the ratio of Firmicutes to Bacteroidetes by reducing the relative amount of Firmicutes [135]. By stimulating the growth of SCFA-producing bacteria, berberine prevents obesity and insulin resistance through the TLR4 signaling pathway [136,137].…”
Section: Herbs and Spicesmentioning
confidence: 99%